REKONSTRUKSI PEMIKIRAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK INSAN KAMIL - Halimatus Shofiyyah; Iyad Suryadi; Pupu Maspupah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to reconstruct the thinking of Islamic Religious Education (PAI) in the formation of insan kamil (perfect human being) through an integrative and contemporary approach. The concept of insan kamil has long been a central aspiration in Islamic educational thought, yet its implementation in modern educational practice remains fragmented and lacks systematic philosophical grounding. Using a qualitative approach with library research methods, this study analyzes the thoughts of three prominent figures al-Ghazali, Muhammad Iqbal, and Hasan Langgulung to examine how each conceptualized the ideal human being and the role of education in realizing it. The findings indicate that al-Ghazali emphasizes the purification of the soul (tazkiyat al-nafs) as the primary foundation of human perfection; Iqbal stresses the development of the self (khudi) through creativity and dynamic engagement with modernity; while Langgulung integrates a psychological and sociological perspective within Islamic education. Synthesizing these three perspectives, this study proposes a reconstructed model of PAI that is rooted in spiritual values, oriented toward the development of individual potential, and responsive to contemporary social challenges. The implication of this reconstruction is that Islamic Religious Education must be reoriented not merely as doctrinal transmission, but as a transformative process that shapes the whole human being intellectually, spiritually, and socially.